Silver complexes with fluoroanthranilic acid isomers: Spectroscopic characterization, antimycobacterial activity and cytotoxic studies over a panel of tumor cells - Manzano, Carlos M.; Nakahata, Douglas H.; Tenorio, Juan C.; Lustri, Wilton R.; Resende Nogueira, Flávia A.; Aleixo, Nadia A.; da Silva Gomes, Pietra S.; Pavan, Fernando R. [UNESP]; Grecco, Julia A. [UNESP]; Ribeiro, Camila M. [UNESP]; Corbi, Pedro P. (Elsevier, 2020)
This manuscript presents three silver(I) complexes with fluoroanthranilic acid (fa) isomers, [Ag(4fa)]n, [Ag(5fa)]n and [Ag(6fa)]n, which were named as Ag4fa, Ag5fa and Ag6fa, respectively. The 1:1 metal/ligand molar composition of the complexes was determined by elemental, thermal and high-resolution mass spectrometric (ESI(+)-MS) analyses. Infrared and 1H, 13C and {15N,1H} nuclear magnetic resonance spectroscopy evidenced the coordination of the fluoroanthranilic acid isomers to silver via the nitrogen atom of the amino group and by the oxygen atoms of the carboxylate group. The structure of the Ag5fa complex was determined by single crystal X-ray diffraction analysis. The complex forms an extended polymeric structure organized in layers with coordination by the amino and carboxylate moieties. Antibacterial activity assays showed that the silver complexes were active against M. tuberculosis (MIC90 between 2.6 and 4.2 µg/mL) and also over S. aureus, B. cereus, E. coli and P. aeruginosa (MIC = 62.25 µg/mL) strains. The complexes have also shown in vitro cytotoxicity over cancer cell lines and selectivity (SI) especially against epithelial colorectal adenocarcinoma cells (IC50 = 2.1 µg/mL and SI > 3). Also, the silver complexes are non-mutagenic, which is essential when considering the development of new bioactive compounds for therapeutic purposes.
Keywords: Antibacterial agents; Antitumor activities; Fluoroanthranilic acid; Infrared; NMR spectroscopy; Silver